2012
DOI: 10.1128/mcb.01142-12
|View full text |Cite
|
Sign up to set email alerts
|

Luman/CREB3 Recruitment Factor Regulates Glucocorticoid Receptor Activity and Is Essential for Prolactin-Mediated Maternal Instinct

Abstract: The hypothalamic-pituitary-adrenal (HPA) axis is a major part of the neuroendocrine system in animal responses to stress. It is known that the HPA axis is attenuated at parturition to prevent detrimental effects of glucocorticoid secretion including inhibition of lactation and maternal responsiveness. Luman/CREB3 recruitment factor (LRF) was identified as a negative regulator of CREB3 which is involved in the endoplasmic reticulum stress response. Here, we report a LRF gene knockout mouse line that has a sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 68 publications
(75 reference statements)
1
40
0
Order By: Relevance
“…Besides its cellular function, the biological role of LRF is largely unknown. Recently, we found a severe maternal behavioral defect in female LRF gene knockout mice accompanied by misregulation of glucocorticoid and prolactin signaling [23]. Our preliminary data also suggest a fertility deficit in these mutant mice (unpublished), suggesting a potential role for LRF in reproduction and related hormonal signaling.…”
supporting
confidence: 61%
“…Besides its cellular function, the biological role of LRF is largely unknown. Recently, we found a severe maternal behavioral defect in female LRF gene knockout mice accompanied by misregulation of glucocorticoid and prolactin signaling [23]. Our preliminary data also suggest a fertility deficit in these mutant mice (unpublished), suggesting a potential role for LRF in reproduction and related hormonal signaling.…”
supporting
confidence: 61%
“…However, the function of CREBRF is minimally characterized, so the mechanisms by which rs373863828 affects these phenotypes are currently unclear. Individual studies have indicated that this transcription factor impacts glucocorticoid signaling, autophagy, unfolded protein response, and starvation resistance, as well as murine decidualization, embryo implantation, and maternal behavior (Audas, Li, Liang, & Lu, 2008; Li et al, 2016; Martyn et al, 2012; Minster et al, 2016; Xue et al, 2016; Yang et al, 2013). Future studies should aim to refine the effect of this variation on the related phenotypes of height, weight, and BMI in other Pacific Island populations, as well as other anthropometric traits.…”
Section: Discussionmentioning
confidence: 99%
“…The potential importance of this variant in organismal energy homeostasis is further supported by the ‘lean’ phenotype of mice 30 and flies 26 lacking the ortholog for this gene. These data, in combination with evidence of positive selection, support a thrifty variant hypothesis for human obesity and underscore the value of examining unique populations to identify new genetic contributions to complex traits.…”
mentioning
confidence: 97%
“…In support of this hypothesis, expression of CREBRF orthologs is highly induced by starvation in all tissues of Drosophila 26,27 as well as in human lymphoblasts 28,29 . Moreover, REPTOR -knockout flies 26 and Crebrf -knockout mice 30 have lower total energy storage and body weight, respectively. Similarly, we found that nutrient starvation of 3T3-L1 preadipocytes rapidly increased Crebrf mRNA levels, which peaked by 4 h at levels 13-fold higher than those seen at 0 h ( P = 1.1 × 10 −16 ) and remained elevated by 5-fold at 24 h after the start of starvation ( P = 4.1 × 10 −14 ) (Fig.…”
mentioning
confidence: 99%